GEOCHEMISTRY AND MINERALOGY OF THE CRETACEOUS WULANTUGA HIGH-GERMANIUM COAL DEPOSIT IN SHENGLI COAL FIELD, INNER MONGOLIA, NORTHEASTERN CHINA - Zhuang X.; Querol X.; Alastuey A.; Plana F.; Lopez-Soler A.; Juan R.; Du G.; Martynov V.V. (My University, 2006)
The occurrence and distribution of minerals, and major and trace elements of the coal #6-1 from the Cretaceous Wulantuga high-germanium coal deposit in Shengli coal field, Inner Mongolia are investigated. The major mineral constituents of coal #6-1 are quartz (15%), kaolinite (4-5%), illite (1%), pyrite (< 1%), feldspars (< 1%), gypsum (weathering product, < 2%) and traces of chlorite. In addition to these phases, traces of scheelite (CaWO4) and weddellite (an oxalate, CaC2O4·2H2O) were also detected by XRD. On the basis of chemical and mineralogical properties, a clear differentiation was found between the upper and lower coal sections: the lower section with higher sulfide mineral content, and the upper one with low sulfur content and with a higher proportion of mineral phases formed/accumulated under oxidizing conditions (quartz and dolomite). This coal seam is highly enriched in Ge, As, W, and Hg (one to two orders of magnitude higher than the usual worldwide coal concentrations), with high contents of Sb, U, Cs, and Be (one order of magnitude higher than the usual worldwide coal concentrations). The geochemical and mineralogical profile patterns of the coal seam were attributed to the development of a basal reduced marsh environment evolving towards a more oxidizing marsh environment in the upper part of the coal seam. This could be related to the evolution from a high water table low moor marsh environment to a high moor marsh into an open water body with a higher detrital influence at the top of the seam. These syngenetic geochemical characteristics are possibly modified by an unusually intensive hydrothermal alteration causing the formation of oxalate minerals and the enrichment in a series of elements such as Cs, Be, U, As, Se, and Hg. © 2005 Elsevier B.V. All rights reserved.
Keywords: CHINA; COAL; GEOCHEMISTRY; GERMANIUM; INNER MONGOLIA; METALS; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая